(untitled) (Baghdad Science Journal, 2004)
The first sign of heart development in mosquito fish starts in an embryo of 0.6mm. long. It appears as two thickenings in the splanchnic mesodermal plates located on both sides of the ventral median line of the embryo under the foregut. From these two thickenings a group of loose cells are detached. These cells represent the heart primordium which develops into the endocardial tube. The endocardial tube appears to be surrounded by the two thickened plates of splanchnic mesoderm. These go to form a heart tube with a double-layered wall. The heart chambers will differentiate in a antero-posterior direction; starting with the bulbus arteriosus then the ventricle followed by the atrium and lastly the sinus venosus. The embryo of 7 mm. long shows that the heart chambers are arranged on a bent line. This bent continues and the heart chambers will occupy the pericardial cavity. In the new born larva the bulbus arteriosus assumes an anterior position, the ventricle has the dorsal, the atrium has the ventral, and the sinus venosus has the posterior position. With the development, the ventricle and the atrium interchange in their positions. This interchange occurs as a result of a rotary motion of 180+ in a clockwise direction. As a result the ventricle occupies a ventral position and the atrium occupies . a dorsal position. Thus the heart takes its final shape as that in the adult fish.